SHH medulloblastoma and very early onset of bowel polyps in a child with PTEN hamartoma tumor syndrome - Caroleo, Anna Maria; Rotulo, Silvia; Agolini, Emanuele; Macchiaiolo, Marina; Boccuto, Luigi; Antonelli, Manila; Colafati, Giovanna Stefania; Cacchione, Antonella; Megaro, Giacomina; Carai, Andrea; De Ioris, Maria Antonietta; Lodi, Mariachiara; et al. (Frontiers in Molecular Neuroscience, 2023)
Phosphatase and tensin homolog (PTEN) hamartoma tumor syndrome (PHTS) is a cancer predisposition syndrome characterized by an increased risk of developing benign and malignant tumors, caused by germline pathogenic variants of the PTEN tumour suppressor gene. PTEN gene variants often present in childhood with macrocephaly, developmental delay, and/or autism spectrum disorder while tumors and intestinal polyps are commonly detected in adults. PHTS is rarely associated with childhood brain tumors with only two reported cases of medulloblastoma (MB). We report the exceptional case of an infant carrying a germline and somatic pathogenic variant of PTEN and a germline and somatic pathogenic variant of CHEK2 who developed a MB SHH in addition to intestinal polyposis.